3D seismic response analysis of shallow foundation resting on sandy soil - Kumar R.; Mohanty S.; Chethan K. (My University, 2025)
In the present study, an attempt has been made to study the response of a shallow foundation resting on medium dense sandy soil under seismic excitation. Numerical analysis of the soil-foundation system has been carried out using 3D finite element software OpenSeesPL. The effect of boundary conditions (shear beam and rigid box type) and the water table (0 m, 1 m and 2 m below the ground surface) on the response of soil-foundation system under seismic excitation have been analysed. The responses of the soil-foundation system are presented in the form of acceleration, displacement, excess pore pressure, excess pore pressure ratio and settlement variations at different locations in the soil domain. The results of the numerical analysis indicate that the peak acceleration, displacement, excess pore pressure and settlement values are found to be more in shear beam type boundary condition than that of a rigid box type boundary condition. Hence, rigid confinement and lower water table can reduce the liquefaction potential of the soil-foundation system under seismic excitation. Copyright © 2019, IGI Global.